2022
DOI: 10.1530/ec-21-0630
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life 6 months after parathyroidectomy for primary hyperparathyroidism

Abstract: Objective: The extent of symptoms due to primary hyperparathyroidism depends on the population being studied. Primary hyperparathyroidism is mainly discovered incidentally through routine laboratory findings. Less is known about patient-experienced improvement following successful parathyroidectomy. The aim of our study was to assess changes in Quality of Life after successful surgery using an SF-36 questionnaire. Design: This is a prospective cohort study based on questionnaires. Methods: Forty consecutive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Similar data were revealed by Christensen et al [17] in a prospective study from 2022 on 40 patients with PHP (median age of 62 years, ranges between 28 and 82; 65% were females). Out of the eight domains of SF-36, six categories showed a statistically significant increase 6 months post-PTx, three of them concerning PCS: VT (p = 0.0001), PF (p = 0.038), RP (p = 0.043), and another three concerning MCS: GH (p = 0.004), SF (p = 0.004), MH (p = 0.0001) [17]. Interestingly, some of the patients were enrolled during the COVID-19 pandemic, which did not seem to affect the study results [17].…”
Section: The Influence Of Parathyroidectomy On Qolsupporting
confidence: 87%
See 3 more Smart Citations
“…Similar data were revealed by Christensen et al [17] in a prospective study from 2022 on 40 patients with PHP (median age of 62 years, ranges between 28 and 82; 65% were females). Out of the eight domains of SF-36, six categories showed a statistically significant increase 6 months post-PTx, three of them concerning PCS: VT (p = 0.0001), PF (p = 0.038), RP (p = 0.043), and another three concerning MCS: GH (p = 0.004), SF (p = 0.004), MH (p = 0.0001) [17]. Interestingly, some of the patients were enrolled during the COVID-19 pandemic, which did not seem to affect the study results [17].…”
Section: The Influence Of Parathyroidectomy On Qolsupporting
confidence: 87%
“…As previously mentioned, PTH-dependent hypercalcemia displays a certain influence on QoL, but not all studies agree on this matter [17,24,25]. For example, Christensen et al [17] did not identify a significant relationship between QoL and calcium levels dynamics, as oppsed to other researchers.…”
Section: Primary Hyperparathyroidism-related Serum Calcium and Qol In...mentioning
confidence: 94%
See 2 more Smart Citations
“…The question of HR-QoL after PTX for PHPT is still a matter of controversy. On the one hand, short-term studies, mostly observational, have suggested an improvement within the first 15 months after PTX using the SF-36 questionnaire 12 , 17 , 37 , 38 . The largest study comes from Weber et al .…”
Section: Discussionmentioning
confidence: 99%